Model Aplikasi Presensi Ekstrakurikuler Siswa Sekolah Menengah Atas Dengan Fitur Face Recognition - Bahar, Bahar; Tama, Rivaldi Jaya; Fadilah, Fadilah (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2026)
Attendance for extracurricular activities in high schools, which is generally still done manually or using signatures, is vulnerable to manipulation by students, such as leaving absences or falsifying attendance. This condition has an impact on the low accuracy of attendance data and less than optimal monitoring of student participation in extracurricular activities. This research aims to design and develop a facial recognition-based extracurricular attendance application model that is capable of automatically identifying students through facial recognition. Student facial recognition uses several main parameters on the face, namely Eyebrows, Eyes, Nose and Mouth. Performance testing on 50 students through five facial component openness scenarios (100%, 75%, 50%, 25%, and 0%). Test results show that the system works consistently in conditions of 100% and 75% open faces, inconsistently in conditions of 50%, and fails to recognize conditions in 25% and 0%. The research conclusions show that the system is effective for use in relatively open facial conditions and has the potential to minimize presence manipulation, so it is suitable for application in digital-based extracurricular attendance management.Keywords: Face Recognition; Extracurricular Presence; Biometric System; Face Identification; Digital Presence Application AbstrakPresensi kegiatan ekstrakurikuler di Sekolah Menengah Atas yang pada umumnya masih dilakukan secara manual atau menggunakan tanda tangan, rentan terhadap manipulasi oleh siswa, seperti titip absen atau pemalsuan kehadiran. Kondisi ini berdampak pada rendahnya akurasi data kehadiran dan kurang optimalnya pengawasan partisipasi siswa dalam kegiatan ekstrakurikuler. Penelitian ini bertujuan untuk merancang dan mengembangkan model aplikasi presensi ekstrakurikuler berbasis face recognition yang mampu mengidentifikasi siswa secara otomatis melalui pengenalan wajah. Pengenalan wajah siswa menggunakan beberapa parameter utama pada wajah, yaitu Alis, Mata, Hidung, dan Mulut. Pengujian performa terhadap 50 siswa melalui lima skenario keterbukaan komponen wajah (100%, 75%, 50%, 25%, dan 0%). Hasil pengujian menunjukkan bahwa sistem bekerja konsisten pada kondisi 100% dan 75% wajah terbuka, tidak konsisten pada kondisi 50%, serta gagal mengenali pada kondisi 25% dan 0%. Simpulan penelitian menunjukkan bahwa sistem efektif digunakan pada kondisi wajah relatif terbuka dan berpotensi meminimalkan manipulasi presensi, sehingga layak diterapkan dalam pengelolaan presensi ekstrakurikuler berbasis digital.